Assessing Financial Impacts of Subclinical Mastitis on Colombian Dairy Farms - Romero, Jaime; Benavides, Efraín; Meza, Carlos (Frontiers in Veterinary Science, 2018)
Bovine mastitis is a dairy cattle disease with high economic impact. Subclinical mastitis (SCM) contributes to most of financial losses. Colombia dairy sector accounts for 2.3% of the Gross Domestic Product – GDP and 24.3% of the livestock GDP. Milk production reaches 6,500 million liters/year from nearly 500,000 cattle farms and is mainly based on small-scale production systems. This study evaluates the financial impact of SCM and the potential for its control in three dairy farm strata in a region in Colombia. The objectives of the study were 1- to determine the perception of farmers about the SCM problem on their farms, 2- to assess prevalence and the financial impact of SCM on farms and in the region, 3- to assess on farm, costs and effectiveness of control methods of SCM. Information about disease management and decision-making process was obtained through a participatory epidemiology workshop and applying a semi-structured survey. A two- stage stratified cross sectional epidemiological study was conducted on dairy cattle from a region with approximately 400 farms and 12,000 cows, with a sample size of 55 farms. Prevalence of SCM was calculated defining a positive cow to the disease when any quarter had a Somatic Cell Count (SCC) higher than 250 ×103 cells/ml. The prevalence of SCM in cows was 55.2%; significant differences were found between strata. Assessment of the financial impact of SCM in terms of milk losses was conducted using spreadsheet models. Milk production losses per farm ranged from 1.3% to 13.5% and the economic impact in the region was estimated over USD $800.000 per year. The financial impact was greater in small and medium sized farms than large farms and it was associated with the severity of SCC per quarter. Principal Component Analysis showed interactions, irrespectively of individual effect and suggested three main groups of control interventions: application of basic milking hygiene practices, increase the level of hygiene practices and veterinary advice and, SCM diagnosis and dry-cow treatment. Lack of information on management and production at farms promotes intuitive decision-making. Further research on deeper understanding of intervention costs and effectiveness is suggested.